FSG301: Laboratory Management / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2020)
This is a management laboratory course which provides a basic knowledge on the laboratory management such as general safety guidelines to ensure a safe environment while working in the laboratory. Topic such as total quality management systems in the laboratory will facilitate the mutual recognition of analytical data between the laboratories and trading partners in a relation to the regulations and international standards.